2005
DOI: 10.3168/jds.s0022-0302(05)72880-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Sources of Vegetable Oils on Performance of High-Yielding Lactating Cows and Conjugated Linoleic Acids in Milk

Abstract: This study was conducted to examine the effects of dietary supplementation with vegetable oils on performance of high-yielding lactating cows and conjugated linoleic acid (CLA) content in milk fat. Twelve lactating Holstein cows in early lactation (30 to 45 d postpartum) were used in a triple 4 x 4 Latin square design. In each period, the cows in each group were fed the same basal diet and received one of the following treatments: 1) control (without oil), 2) 500 g of cottonseed oil, 3) 500 g of soybean oil, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 16 publications
6
37
0
7
Order By: Relevance
“…Long-chain unsaturated FA appear to be more toxic to ruminal bacteria as they can attach to lipid bilayers in bacterial membranes (because of their hydrophobic and amphiphilic nature). The longer the chains, and the more double bonds, the easier it is for FA to attach and destroy membranes of bacteria (Zheng et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain unsaturated FA appear to be more toxic to ruminal bacteria as they can attach to lipid bilayers in bacterial membranes (because of their hydrophobic and amphiphilic nature). The longer the chains, and the more double bonds, the easier it is for FA to attach and destroy membranes of bacteria (Zheng et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, neither Kitessa et al (2001), with fish oil in goats, nor Allred et al (2006), with fish and soy oils in cows, observed significant differences. Finally, studying the effects of different types of vegetable oils used as supplements, Zheng et al (2005) and Bell et al (2006), in cows, and Zervas et al (1998) and Zhang et al (2006), in dairy ewes, observed that vegetable oils sharply decreased the percentage of milk fat.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, not much is known on how sow nutrition affects colostrum yield. Dietary fat from different sources are commonly included in lactation diets to improve milk yield of sows (Boyd et al, 1982;Lauridsen and Danielsen, 2004), and CLA, a bioactive FA, is known to impact mammary gland metabolism and increase the milk yield of dairy cows (Zheng et al, 2005). It was therefore reasonable to assume that inclusion of dietary CLA could increase colostrum production, but sows fed with 1.3% CLA (an equal mixture of cis-9/trans-11 and trans-10/cis-12 isomers) from day 108 of gestation until parturition tended to produce less colostrum (409 v. 463 g; P = 0.07) and more piglets died or had to be moved to other sows during the 1 st week of lactation to ensure their survival (17.6% v. 7.8% in the control group; P = 0.04; Krogh et al, 2012) compared with control sows.…”
Section: Sow Nutrition and Piglet Survivalmentioning
confidence: 99%